2023
DOI: 10.1128/spectrum.01457-23
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome and Metabonomic Profile Predict Early Remission to Anti-Integrin Therapy in Patients with Moderate to Severe Ulcerative Colitis

Abstract: It is reported that patients with ulcerative colitis (UC) have low response rates to anti-integrin medications in the latest VARSITY study. Therefore, our primary goals were to discover differences in the gut microbiome and metabonomics patterns between early remission and nonremission patients and to explore the diagnostic value in predicting clinical remission to anti-integrin therapy accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Verrucomicobiota has been reported to be one of the phyla present in the human gut, which has only one cultivated intestinal representative, Akkermansia muciniphila ( Derrien et al, 2017 ). Studies have shown that the abundance of Verrucomicrobiota was significantly lower in UC patients with active phase, while significantly higher in the remission phases than that of the healthy control group at the phylum level ( Zhu et al, 2022 ; Liu J. et al, 2023 ). Therefore, Verrucomicrobiota may offer potential prospects for future treatment of human UC.…”
Section: Discussionmentioning
confidence: 96%
“…Verrucomicobiota has been reported to be one of the phyla present in the human gut, which has only one cultivated intestinal representative, Akkermansia muciniphila ( Derrien et al, 2017 ). Studies have shown that the abundance of Verrucomicrobiota was significantly lower in UC patients with active phase, while significantly higher in the remission phases than that of the healthy control group at the phylum level ( Zhu et al, 2022 ; Liu J. et al, 2023 ). Therefore, Verrucomicrobiota may offer potential prospects for future treatment of human UC.…”
Section: Discussionmentioning
confidence: 96%
“…Open access of stool showed significantly higher levels of SCFAs including butyrate in those achieving week 14 remission (defined as total Mayo score ≤2, all subscores ≤1) vs non-remitters. 19 Combining metabolite data (SCFA levels for butyrate and isobutyric acid) with microbial profile data predicted anti-integrin response with an AUC of 0.961. While these previous studies are important first steps to using gut microbial signatures in stratified treatment algorithms, they were mostly underpowered, examined single treatments, used different sequencing technologies and produced heterogeneous non-overlapping results.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Regardless of relapse status, IBD patients have lower isobutyrate levels than healthy individuals ( 106 ). Furthermore, isobutyrate and Verrucomicrobiota could serve as markers for diagnosing UC remission ( 108 ). Additionally, hexanoate might serve as a predictive indicator for CD patient relapse risk ( 25 ).…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
“…Levels of butyrate and substrates are correlated with the remission outcomes of Infliximab treatment ( 214 ). Similarly, butyric acid and isobutyric acid can serve as biomarkers for patient responses to Vedolizumab ( 108 ). Furthermore, glucocorticoids, such as prednisolone, can directly reduce luminal lipid mediators like PGE2 and LTB4, improving IBD symptoms ( 215 , 216 ).…”
Section: Therapeutic Approaches Based On Fatty Acidsmentioning
confidence: 99%